Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Le blanchiment de l’intersectionnalité - Bilge, Sirma (Recherches féministes, 2015)
Le féminisme académique entretient une relation ambiguë avec l’intersectionnalité qu’il encense et discipline du même souffle. Par un ensemble de discours et de pratiques, la pensée critique raciale est évacuée de l’appareillage actuel de l’intersectionnalité et les personnes racialisées comme productrices des savoirs intersectionnels se trouvent marginalisées dans les débats et les espaces académiques contemporains. La science sert souvent d’alibi dans de telles opérations. Ces dernières font l’objet de l’analyse de l’auteure qui les conceptualise en tant que blanchiment de l’intersectionnalité.
Keywords: 1900-1999; afro-féminisme; approches et analyses; com5170; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem3300; fem7000; fem9000; féminismes noirs; intersectionnalité; lit3220; lit4700; premier cycle; périodes historiques; ressource en ligne; savoirs; sciences humaines; sociologie; systèmes d'oppressions

L’intersectionnalité, un mot à la mode. Ce qui fait le succès d’une théorie féministe - Davis, Kathy (Les cahiers du CEDREF, 2015)
Keywords: approches et analyses; concept; discipline; intersectionnalité; ressource en ligne; sciences humaines; sociologie; théories féministes

Traversés féministes transnationales: du néolibéralisme et de la critique radicale - Mohanty, Chandra Talpade (Les cahiers du CEDREF, 2015)
Qu’est-il arrivé à la recherche et à la théorie féministe dans notre culture universitaire néolibérale ? Les transformations globales et nationales dans l’activisme du mouvement social et les projets de recherche féministe ont-ils dépolitisé les projets intellectuels féministes, antiracistes, femmes-de-couleur1 et transnationaux ? J’examine ici les diverses façons dont mon propre travail a voyagé et ce qu’il a perdu (et trouvé) en étant traduit dans différents contextes, pour offrir quelques réflexions sur les effets des paysages géopolitiques néolibéraux obsédés par la sécurité nationale et sur les cadres intellectuels postmodernes, ainsi que sur la théorisation féministe intersectionnelle et le travail de solidarité transnationale. La façon dont mon travail a été adapté et développé dans certaines communautés de chercheuses et d’activistes féministes marginalisées me semble offrir notamment d’intéressantes leçons pour nous toutes, les féministes universitaires, en indiquant les limites des projets de savoirs féministes postmodernes dans l’Université néolibérale.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; antiracisme; approches et analyses; capitalisme; cours; discipline; dépolitisation; féminisme décolonial; féminisme postmoderne; histoire et politique; intersectionnalité; militance; néolibéralisme; pol4212; postmodernisme; premier cycle; périodes historiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; université néolibérale